Incidence of Primary Complications Afterwards Modified Radical Mastectomy in Breast Cancer - Hifsa Ali, Shoaib Muhammad, Varda Balouch, Maria Shaikh, Pooja Kumari (Pakistan Journal of Medical & Health Sciences, 2022)
The cancer of breast is the 2nd leading source of cancer death in females. A modified radical mastectomy encompassed the combines removal of the axillary lymph nodes with all breast tissue removal from the affected breast. The most common complication of surgery is formation of seroma. Inadequate data is accessible on this topic. This analysis therefore provides valued information on this problem associated with infection of wound. Objective: To govern the initial complications after radical modified mastectomy in women with cancer of breast. Study Design: A descriptive case study. Place and Duration: In the Surgical department of Muhammad Teaching Hospital, Peshawar for the duration of one-year from November 2020 to October 2021. Methods: This descriptive case study was conducted at the surgical department of Muhammad Teaching Hospital, Peshawar for the duration of one-year from November 2020 to October 2021. The estimated sample size had an incidence of 18%, margin of error = 10% and CI = 95% of the sample size required is 62 patients. The sampling method used was non-probability purposive. Patients who met the selection criteria underwent a modified radical mastectomy with the prior conversant written consent. The patients were discharged home on the second day of surgery and were monitored weekly for the first 6 weeks at the clinic for primary complications such as seroma formation and wound infection. All related demographic data such as clinical information and age such breast cancer staging with possible complications were recorded at the culmination of 6-weeks. Data were entered into SPSS software version 21 and analyzed. Results: The study included 62 females with a modified radical mastectomy for breast cancer who fully met the criteria of inclusion. 46.10± 13.02 years was the patients mean age with 20-75 years age range. The mean postoperative day of infection in wound was 4.60± 1.9 days and the mean postoperative day for seroma was 9.21± 3.98 days. Stage II breast cancer was diagnosed in 44 patients (70.9%) and stage I breast cancer in 18 patients (29.1%). Wound infection was observed in 5 patients (8.1%), while 16 patients (25.8%) experienced complications related to seroma formation. Conclusion: This study showed that complications such as infection in the wound are significantly lower, but the incidence of seroma is consistent with nationwide studies that justify novel interferences to reduce the rate of these complications. Keywords: Modified radical mastectomy, Seroma, Wound infection.